The Influence of Independence, Experience, and Competence on Audit Quality Mediated by the Effectiveness of E-Audit - Susanto, Hendra; Lusttilanang, Pius; Suwarno, Suwarno; Restianto, Yanuar (Research Horizon, 2023)
The widespread instances of violations of examination standards and the failure to uphold ethical values among auditors have raised public doubts about auditors. The quality of audits serves as a benchmark for assessing the financial management soundness of an entity under examination. On the other hand, e-audit is expected to help auditors improve audit quality. The purpose of this research is to comprehend and analyze the effectiveness of E-Audit on audit quality at the Audit Board of the Republic of Indonesia. The research was conducted using a quantitative approach, with 196 respondents selected through purposive sampling. Structural Equation Modeling (SEM) was employed as the data analysis technique. The results of this research indicate that independence, experience, and competence have a positive effect on the effectiveness of E-Audit and audit quality. Furthermore, the effectiveness of E-Audit can mediate the influences of independence, experience, and competence on audit quality.